FP5 and Slovenian participants - towards FP6 - Jenko, Bojan (Materiali in tehnologije, 2001)
In the Fifth Framework Programme (FP5) of the EU is research activities prepared by the European Commission, Slovenia, as an associated state, has been eligible to be a participating partner. FP5 is closing at the end of 2001/begining of 2002. Slovenian participants have been very successful, sometimes with a success rate even exceeding the European average. The success rate has varied from programme to programme and from call to call. Autumn 2001 calls, especially for NAS (Newly Associated States, including Slovenia), were dedicated to add extra partners from pre-accession countries to the on-going projects, for fascilitating the integration of NAS into the European Research Area, from pre-accession countries to the on-going projects, for fascilitating the integration of NAS into the European Research Area, for Strategic action on training/excellence, etc. The application procedure was simplified. The information including procedures, application forms and eligible projects for joining were available on the EC CORDIS website (http://www.cordis.lu/fp5/home.html), and accessible from the Ministry of Education, Science and Sport website, too (http://www.mzt.si/mzt/med/5okvp/index.html). Some calls for SMEs will close in spring 2002. The European Union is establishing the European Research Area (ERA) with new priorities, new procedures, new challenges and new opportunities. At present, the European Commission is preparing the next Framework Program, FP6, for the period 2002-2006 in order to stimulate it. The proposal for FP6 began in the European Parliament's procedures in second the half of 2001.
Keywords: okvirni programi; evropski programi; raziskovalna dejavnost; European Union; Evropska unija; Slovenia; Slovenija